MENIMBANG KEUMUMAN LAFZH ‘ÂMM DAN MUTHLAQ DALAM MENGUNGKAP MAKNA NASH SYAR’Î - Abdul Jalil (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Understanding what is desired by Allah from the texts of the Qur’an that which is essentially many debatable than the immutable have led to a variety of concepts generated by the ushûliyyûn, like ‘âmm and muthlaq. These two concepts are very numerous and often intersect in the texts of the Qur’an, because the sturcture of the words on the legal source are mostly composed of ‘âmm and muthlaq words. Both have the differences and similarities in coverage breadth of its meaning. First, differences can be seen in the ‘âmm word covering the whole meaning of syar'î texts has many forms and varieties. While the muthlaq word consists only of nakirah word both singular and plural form. The other hand, the difference that in generality of ‘âmm is syumûlî and generality of muthlaq is badalî. In addition, the generality of ‘âmm from afrâd side (components), while the generality of muthlaq is from characteristic side. Secondly, the range of ‘âmm word is wider than the muthlaq word, due to the shape and variety of ‘âmm word more than the muthlaq word, ‘âmm word able to spend the amount of units more than the muthlaq word since the generality ‘âmm word on the side of component units, while the generality of the muthlaq word located on the side of characteristic.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.731